Human resource capabilities as innovation strategy: Impact on business performance of batik SMEs in Indonesia - Agustinah, Fedianty; Tampubolon, Liosten Rianna Roosida Ully; Sukesi,; Budidharmanto, Lexi Pranata; Muhajir, Ali (International Journal of Management and Sustainability, 2025)
This study explores the role of human resource capabilities as a catalyst for innovation strategy and their influence on the performance of Batik Small and Medium Enterprises (SMEs) in East Java, Indonesia. Using a quantitative approach, data were collected from 249 Batik SME owners and analyzed through Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that human resource competencies significantly and positively affect various dimensions of innovation strategy, including product, process, technological, organizational, and service innovations. These innovation strategies, in turn, enhance firm competitiveness and performance. Furthermore, the relationship between innovation and performance is moderated by marketing strategy, underscoring its strategic importance in maximizing innovation outcomes. Importantly, the study highlights how human resource-driven innovation promotes sustainability by supporting environmentally responsible practices, social inclusion, and cultural heritage preservation. By integrating the Resource-Based View and Dynamic Capabilities theories, this research demonstrates that human capital, particularly in traditional, labour-intensive sectors, forms the basis of multidimensional and sustainability-oriented innovation. The study contributes to the innovation literature by showing that different types of innovation follow distinct paths toward competitiveness and performance. It also challenges assumptions that marketing strategies always amplify innovation outcomes. In the context of sustainability research, the study underscores how culturally rooted human innovation in Batik SMEs fosters economic resilience, environmental consciousness, and socio-cultural continuity. These insights offer practical implications for SMEs, policymakers, and development agencies aiming to enhance the competitiveness and sustainability of heritage-based industries in evolving market landscapes.